Correlation Between Matrix Metalloproteinases With Coronary Artery Lesion Caused by Kawasaki Disease - Tian, Fang; Ma, Linxi; Zhao, Renbing; Ji, Lijuan; Wang, Xiufen; Sun, Wenli; Jiang, Yu (Frontiers in Pediatrics, 2022)
This study was designed to clarify the role of matrix metalloproteinases (MMPs) in coronary artery lesions (CAL). Serum samples were acquired from healthy, febrile, and Kawasaki disease (KD) children with or without CAL. Standard blood parameters were examined and enzyme-linked immunosorbent assay (ELISA) was used to assess the levels of MMP-2 and MMP-9. Intravenous immunoglobulin (IVIG) therapy was conducted on the KD patients and the changes of MMPs before and after treatment were compared. The correlations between MMP levels and clinical parameters were also evaluated. Compared to febrile and healthy controls, KD patients demonstrated clinical signs characteristic of abnormal immunoregulation. However, the clinical parameters of KD patients with or without CAL were not significantly different. MMP-2 and MMP-9 levels, however, were significantly higher in KD patients with CAL than those without CAL. IVIG treatment effectively downregulated the levels of MMPs in KD patients, which was more prominent in those with CAL. Significant correlations were found between MMP levels and some clinical parameters of KD, such as fever time, white blood cell count, etc. The upregulation of MMPs significantly correlates with coronary artery aneurysms (CAAs) in KD patients, making it important biomarkers of CAL in KD patients.